Ultrasound vector flow imaging during veno-arterial extracorporeal membrane oxygenation in a thoracic aorta model - Yambe, Kenichiro; Ishii, Takuro; Yiu, Billy Y. S.; Yu, Alfred C. H.; Endo, Tomoyuki; Saijo, Yoshifumi (Journal of Artificial Organs, 2024)
In veno-arterial extracorporeal membrane oxygenation (VA-ECMO) treatment, the mixing zone is a key hemodynamic factor that determines the efficacy of the treatment. This study aimed to evaluate the applicability of a novel ultrasound technique called vector flow imaging (VFI) for visualizing complex flow patterns in an aorta phantom under VA-ECMO settings. VFI experiments were performed to image aortic hemodynamics under VA-ECMO treatment simulated in an anthropomorphic thoracic aorta phantom using a pulsatile pump (cardiac output: 2.7 L/min) and an ECMO pump with two different flow rates, 0.35 L/min and 1.0 L/min. The cardiac cycle of hemodynamics in the ascending aorta, aortic arch, and descending aorta was visualized, and the spatio-temporal dynamics of flow vectors were analyzed. VFI successfully visualized dynamic flow patterns in the aorta phantom. When the flow rate of the ECMO pump increased, ECMO flow was more dominant than cardiac output in the diastole phase, and the speed of cardiac output was suppressed in the systole phase. Vortex flow patterns were also detected in the ascending aorta and the arch under both ECMO flow rate conditions. The VFI technique may provide new insights into aortic hemodynamics and facilitates effective and safe VA-ECMO treatment.